Is diabetes an acquired disorder of reactive glucose metabolites and their intermediates? - Fleming, Thomas; Cuny, Jeanne; Nawroth, G.; Djuric, Zdenka; Humpert, Per Magnus; Zeier, Martin; Bierhaus, Angelika; Nawroth, Peter Paul (Diabetologia, 2012)
Aims/hypothesisWe hypothesised that diabetic patients would differ from those without diabetes in regard to the handling of glucose-derived reactive metabolites, evidenced by triosephosphate intermediates (TPINT) and methylglyoxal (MG), irrespective of the type of diabetes, plasma glucose level or HbA1c value.MethodsTo test this hypothesis, erythrocytes were isolated from patients with type 1 (n = 12) and type 2 (n = 12) diabetes with varying blood glucose and HbA1c levels. These were then compared with erythrocytes isolated from individuals without diabetes (n = 10), with respect to MG, as determined by HPLC, and TPINT, as determined by endpoint enzymatic assays.ResultsThe concentrations of intracellular TPINT and MG were significantly elevated in erythrocytes from diabetic patients. Normalisation of either TPINT or MG to intracellular glucose concentration (nmol glucose/mgHb) confirmed that erythrocytes from diabetic patients accumulated more reactive metabolites than did those from healthy controls.Conclusions/interpretationDiabetic patients can be characterised by an increased formation of TPINT and MG. The 25-fold increase of MG in type 1 and the 15-fold increase in type 2 diabetes, together with a several-fold increase in TPINT and decreased glyceraldehyde-3-phosphate dehydrogenase activity even under normal glucose conditions, imply that normalising glucose level cannot completely prevent late diabetic complications until this acquired error of metabolism has been restored.
Gesehen am 14.11.2018